Evaluation the effect of posterior sub-capsular cataract on the refractive state of eye - Srivastava, Namrata; N. Dwivedi, P.; Aswad, Syed (International Journal of Research in Medical Sciences, 2023)
Background: Cataract refractive errors are caused by cataracts. It can go up to several dioptres (D). Correction of expected refractive errors during cataract surgery by altering the axial length measurement. Determine the effect of posterior sub-capsular cataracts on the eye’s refractive status. Methods: 112 patients with posterior sub-capsular cataracts participated in the study. The most common refractive error found in PSC was astigmatism, followed by myopia. The study was conducted at Angel Eye Institute of Ophthalmology; Kanpur U.P. The refractive status of eyes with posterior sub-capsular cataracts was determined using retinoscopy and subjective refraction. Biometry is done by A-scan and keratometer. Results: A total of 112 patients were included in this study. Of these, 27 (26.5%) were males and 75 (73.5%) were females. The Patient’s age was about 60 years. The results showed that the refractive errors caused by posterior sub-capsular cataracts were mainly myopic astigmatism (97. 1%) and spherical myopia (2.9%), 0.16SD. The mean value of myopic astigmatism in patients with PSC was (1.7D, 15.7%), 0.93 SD and the mean value of spherical myopia was (0.1 D, 2.9%), 0.67 SD. Mean uncorrected visual acuity was 1 log MAR and 1.6 SD. The mean corrected visual acuity was 0.3 log MAR and 1.2 SD. Conclusions: The most significant refractive error in PSC was astigmatism, followed by myopia. These findings may help clarify the type of refractive error in patients with PSC and the prediction of ocular vision outcome.